COMPARATION BETWEEN SYNONYM IN INDONESIAN LANGUAGE AND CHINESE LANGUAGE - LESTARI, DIAN; PUJIASTUTI, INDAH (Jurnal Kiprah, 2016)
(Language is the one of telekomunication system.Now Chinese Language not only use in China but also in internasional too. Some people when learn foreign languaget,they face many problems, expecially If that language different from their mother language.This scripsion discuss about comparation of Chinese language,especially in synonym meaning.I do survey for help Indonesian student to learn more especially in Grammer.)